Modeling Brutian pine productivity in Aydın - Kuyucak district - Hüseyin Keçelioğlu; Özdemir Şentürk (Turkish Journal of Forestry)
In order to ensure the sustainability of forest resources, it is critical to realize appropriate forestry practices in forest areas. In this context, the development of productivity models of main trees is of great importance. This study aimed to determine the regions with high and low site index potential for the site properties of the species by modeling the productivity of Brutian pine species. In order to model the productivity of Brutian pine, at least 3 plus trees were determined in each sample area of 20 x 20 m. Using the data obtained from the plus trees, the site index values of Brutian pine in each sample area were calculated. Then, the process of establishing environmental and climatic variables was completed and modeling of Brutian pine productivity was carried out using multiple regression analysis and regression tree method. As a result of the modeling, elevation, annual precipitation and heat load variables structured the model. The highest site index value was obtained where the annual precipitation was above 470 mm, at the elevations with higher heat load and where the elevation was below 326 m. Due to intensive agricultural activities and significant anthropogenic impacts in the Büyük Menderes Plain, the site index values obtained were relatively low. The fact that the Brutian pine stands in the study area are in poor site index or degraded stands supports the results obtained. It is predicted that forestry activities such as interplant, afforestation or regeneration to be carried out in such areas will contribute to restoring the health of the stands and transforming them into better quality and will guide the practitioners in this process. In addition, it is obvious that it will help practitioners in ensuring the sustainability of forest areas, ecosystem restoration, conservation and planning processes.